Solar and Space Weather Radiophysics Current Status and Future Developments - Gary, Dale E.; Keller, Christoph U.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The book explores what can be learned about the Sun and interplanetary space using present-day and future radio observations and techniques. The emphasis is on interpretation of radio data with high spatial and spectral resolution, motivated by the planned construction of a new, powerful, solar-dedicated radio array called the Frequency Agile Solar Radiotelescope (FASR). The book is unique in exploring a broad frequency range, which corresponds to heights ranging from the low solar atmosphere out to the Earth. The book contains a thorough review of the entire field of solar and Space Weather radio research; gives background information suitable for advanced undergraduates, graduates, and researchers in solar and Space Weather research and related fields; and looks at what new results may be expected in the next two decades with FASR and other new instruments now under development. The individual chapters are written by international experts in each topic, and although each chapter may be read as a stand-alone article, the ordering of the chapters and the topical development makes the book readable from beginning to end, to provide an excellent understanding of the field as a whole.
Solar and Solar Radio Effects on Technologies -- Overview of Solar Radio Physics and Interplanetary Disturbances -- The Frequency Agile Solar Radiotelescope -- Radio Spectral Diagnostics -- Coronal Magnetic Field Measurements Through Gyroresonance Emission -- Coronal Magnetic Field Measurements Through Bremsstrahlung Emission -- Coronal Magnetic Field Measurements Through Quasi-Transverse Propagation -- Overview of Solar Flares -- Electron Transport During Solar Flares -- Decimeter Burst Emission and Particle Acceleration -- Radio Observations of Coronal Mass Ejections -- Tomographic 3D-Modeling of the Solar Corona with FASR -- Coronal Diagnostics with Coordinated Radio and EUV/Soft X-Ray Observations -- Radio Observations of the Quiet Sun -- Interplanetary Radio Bursts -- Solar Radar -- Three-Dimensional Tomography of Interplanetary Disturbances.
Keywords: PHYSICS; ASTRONOMY; ASTROPHYSICS; PHYSICS; EXTRATERRESTRIAL PHYSICS, SPACE SCIENCES; ASTRONOMY